2009
DOI: 10.1021/es801482p
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Use Drinking Water Devices for Assessing Microbial Contamination in Finished Water and Distribution Systems

Abstract: The objective of this study was to develop a method to monitor the microbial quality of treated drinking water at the tap utilizing point-of-use filter systems that are placed in water vending machines. Such vending machines have high-volume water throughput and allow for an evaluation of the occurrence of human enteric pathogens and fecal indicator bacteria in tap water over extended time periods. Seeded experiments, using Escherichia coli and bacteriophage MS-2, were performed on (i) new filters, (ii) artifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…Outbreaks of E. coli O157:H7 infection have been associated with the consumption of foods of animal origin, such as undercooked beef, 8 improperly pasteurized milk, 9 or contaminated water. 10 It is estimated that these bacteria cause thousands of foodborne illnesses and hundreds of hospitalizations and deaths worldwide each year. 11 It is very important to monitor pathogenic E. coli strains and stop their growth by simple and novel means.…”
mentioning
confidence: 99%
“…Outbreaks of E. coli O157:H7 infection have been associated with the consumption of foods of animal origin, such as undercooked beef, 8 improperly pasteurized milk, 9 or contaminated water. 10 It is estimated that these bacteria cause thousands of foodborne illnesses and hundreds of hospitalizations and deaths worldwide each year. 11 It is very important to monitor pathogenic E. coli strains and stop their growth by simple and novel means.…”
mentioning
confidence: 99%
“…This study demonstrated that POU devices have the ability to reduce the concentration of a diversity of emerging organic chemical contaminants in potable water, complementing the removal of metals, inorganics, and microbes researched by others (Sato et al 2011, Deshomes et al 2010, Miles et al 2009). Furthermore, these devices provide an additional barrier to accidental or intentional contamination that may occur in the distribution system, such as cross-connections, loss of pressure, or acts of terrorism (Zhong et al 2012).…”
Section: Resultsmentioning
confidence: 54%
“…A POU treatment device is any unit that is designed to improve water quality by providing a barrier against both microbial and chemical contaminants in water within a home (Mintel 2011, Miles et al 2009, Sobsey et al 2008, Esrey et al 1991. Several configurations of POU devices are commercially available, and technologies within a POU type device can be configured for a particular water quality.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on over 500 wells around the U.S. showed that 10-42% of groundwater supply wells are contaminated with enteric viruses [10]; 95% of all individual and small groundwater systems violate one or more primary and secondary drinking water standards in Arizona [11]; and 52% of all point-of-use carbon filters contain an enteric organism after 3 months of use in a municipal system [12]. Approximately 80% of consumer complaints about tap water quality originate in the consumer's home distribution system [4], indicating that management of water quality problems cannot easily be addressed from a single central location.…”
Section: Waterborne Pathogensmentioning
confidence: 99%